Association of body mass index with knee cartilage damage in an asymptomatic population-based study - Alvin Keng; Eric C. Sayre; Ali Guermazi; Savvakis Nicolaou; John M. Esdaile; Anona Thorne; Joel Singer; Jacek A. Kopec; Jolanda Cibere (BMC Musculoskeletal Disorders, 2017)
Abstract Background Cartilage changes are an important early finding of osteoarthritis (OA), which can exist even before symptoms. Our objective was to determine the prevalence of knee cartilage damage on magnetic resonance imaging (MRI) in an asymptomatic population-based cross-sectional study and to evaluate the association of body mass index (BMI) with cartilage damage. Methods Subjects, aged 40-79 years, without knee pain (n = 73) were recruited as a random population sample and assessed for BMI (kg/m2), including current BMI (measured), past BMI at age 25 (self-reported) and change in BMI. Knee cartilage was scored semi-quantitatively (grades 0-4) on MRI. In primary analysis, cartilage damage was defined as ≥2 (at least moderate) and in a secondary analysis as ≥3 (severe). We also conducted a sensitivity analysis by dichotomizing current BMI as <25 vs. ≥25. Logistic regression was used to evaluate the association of each BMI variable with prevalent MRI-detected cartilage damage, adjusted for age and sex. Results Of 73 subjects, knee cartilage damage ≥2 and ≥3 was present in 65.4% and 28.7%, respectively. The median current BMI was 26.1, median past BMI 21.6, and median change in BMI was a gain of 2.8. For cartilage damage ≥2, current BMI had a non-statistically significant OR of 1.65 per 5 units (95% CI 0.93-2.92). For cartilage damage ≥3, current BMI showed a trend towards statistical significance with an OR of 1.70 per 5 units (95% CI 0.99-2.92). Past BMI and change in BMI were not significantly associated with cartilage damage. Current BMI ≥ 25 was statistically significantly associated with cartilage damage ≥2 (OR 3.04 (95% CI 1.10-8.42)), but not for ≥3 (OR 2.63 (95% CI 0.86-8.03)). Conclusions MRI-detected knee cartilage damage was highly prevalent in this asymptomatic population-based cohort. We report a trend towards significance of BMI with cartilage damage severity. Subjects with abnormal current BMI (≥25) had a 3-fold increased odds of cartilage damage ≥2, compared to those with normal BMI. This study lends support towards the role of obesity in the pathogenesis of knee cartilage damage at an asymptomatic stage of disease.